Estudo da interação molecular de retrovírus endógenos humanos e antígenos da mielina com anticorpos - Luca, Vanessa de (2018)
Multiple sclerosis (MS) is an inflammatory, demyelinating and autoimmune disease of the central nervous system. There is evidence that demyelination may be related to the production of autoreactive antibodies against myelin sheath proteins, particularly the myelin oligodendrocyte glycoprotein (MOG). Despite the etiology of MS remains unknown, it might be due to a sum of factors, such as immune system disruption, genetic susceptibility, and environmental factors, of which viral infections are included as proposed viral triggers for the disease. Therefore, human endogenous retrovirus type W (HERV-W) has been studied in MS, from the detection of proteins of the HERV-W envelope gene in patients with the disease. Infections from viruses may be responsible for triggering autoimmunity in MS through molecular mimicry, which consists in the cross-recognition of the immune system, which begins to recognize self-components as antigens because of the similarity to infectious agents. Due to the relevance of etiological aspects to the comprehension of the mechanisms of action of the diseases, the Atomic Force Microscope (AFM) was used to investigate the molecular mimicry theory in MS. For this, MOG peptide sequences similar to HERV-W protein were analyzed.These peptide sequences were subjected to the interaction with anti-HERV-W antibodies applying atomic force spectroscopy and optical detection with silver nanoparticles, aiming to evaluate the molecular interaction and the possible occurrence of molecular mimicry. The obtained results are promising and have revealed the molecular recognition and cross-reactivity of the anti-HERV-W antibody with specific HERV-W and MOG epitopes.